Criteria for assessing the effectiveness of transport power plants decarbonisation in accordance with implementation of the sustainable development concept - Marchenko, Andriy Petrovych; Parsadanov, Igor Volodymyrovych (Національний технічний університет "Харківський політехнічний інститут", 2024)
The directions of restoration and further development of the energy sector in Ukraine are considered in accordance with power plants with internal combustion engines, taking into account the widespread implementation of the Sustainable Development concept, which allows solving existing modern social, economic and environmental problems. For Ukraine, taking into account the economic opportunities and selected priorities for the chosen path of development, it is necessary at this time to choose gradual and specific directions to implement the Sustainable Development concept. The most priority areas of practical implementation of the concept are determined and it is indicated that the effectiveness of this implementation is associated with the development of the industry on the basis of the fourth and fifth industrial revolutions (Industry 4.0 and Industry 5.0).

Напрямки відновлення та подальшого розвитку енергетики в Україні розглянуто відповідно до енергетичних установок з двигунами внутрішнього згоряння із врахуванням поширеного впровадження концепції «Сталий розвиток», що дозволяє вирішувати існуючі сучасні соціальні, економічні і екологічні проблеми. Для України з урахуванням економічних можливостей і обраних пріоритетів щодо обраного шляху розвитку в цей час необхідно обирати поступові і конкретні напрямки реалізації концепції сталого розвитку. Визначені найбільш пріоритетні напрямки практичної реалізації концепції та вказано, що ефективність цієї реалізації пов’язана із розвитком індустрії на основі четвертої та п'ятої промислових революцій (Індустрія 4,0 і Індустрія 5.0).
Критерії оцінювання ефективності декарбонізації силових установок транспорту
Keywords: ecological components; internal combustion engines; decarbonization; exhaust gases; thermal pollution; електростанції; декарбонізація; навколишнє середовище; теплове забруднення; двигуни внутрішнього згоряння